"God's land is vast". Attitudes and practices of Moroccan Muslims regarding burial and repatriation of the deceased. (2nd January 2019) - Ahaddour, Chaïma; Van den Branden, Stef; Broeckaert, Bert
Abstract: The aim of this article is fourfold. First, we seek to elicit the attitudes and practices of middle-aged and elderly Moroccan Muslim women towards burial and repatriation of the deceased. Second, we aim to identify whether differences are observable between middle-aged and elderly women's attitudes and practices. Third, we aim to explore the role of religion in their attitudes and practices. Fourth, we seek to document how the real-world attitudes and practices of our participants relate to the normative Islamic views. Qualitative empirical research was conducted with a sample of middle-aged and elderly Moroccan Muslim women living in Antwerp (Belgium) ( n = 30) and with experts in the field ( n = 15). Our study shows that theological and eschatological considerations play a central role in Moroccan Muslim's attitudes and practices regarding burial. A large majority of our participants opt for repatriation to the country of origin due to socio-emotional (attachment to family and territory), religious and financial reasons. One third of our participants – mainly middle-aged – would prefer burial in Belgium to stay close to their children and to ensure remembrance through grave visits. We did not find a more secular practice or understanding of burial among middle-aged women. We found striking similarities between our participants' views and normative Islamic views.